The story of the Milky Way : a Cherokee tale - Bruchac, Joseph, 1942- (Dial Books for Young Readers, 1995)
When cornmeal is stolen from an elderly couple, the others in a Cherokee village find a way to drive off the thief, creating the Milky Way in the process.